2020
DOI: 10.1039/c9ra07971h
|View full text |Cite
|
Sign up to set email alerts
|

CAY10683 and imatinib have synergistic effects in overcoming imatinib resistance via HDAC2 inhibition in chronic myeloid leukemia

Abstract: Imatinib (IM) is utilized for targeting the BCR–ABL fusion protein and as such, chronic myeloid leukemia (CML) is considered to be a curable disorder for which patients can achieve a long survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…SCA, a powerful and specific HDAC2 inhibitor, has been demonstrated to effectively suppresses tumour progression both in vitro and in vivo. 48 , 49 In our study, aberrant HDAC2 overexpression led to the transcriptional silencing of NLRP3 and suppressed cancer cell pyroptosis. Targeting HDAC2 with the small‐molecule inhibitor SCA increased the efficacy of anticancer drugs in xenografts and PDX models.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…SCA, a powerful and specific HDAC2 inhibitor, has been demonstrated to effectively suppresses tumour progression both in vitro and in vivo. 48 , 49 In our study, aberrant HDAC2 overexpression led to the transcriptional silencing of NLRP3 and suppressed cancer cell pyroptosis. Targeting HDAC2 with the small‐molecule inhibitor SCA increased the efficacy of anticancer drugs in xenografts and PDX models.…”
Section: Discussionsupporting
confidence: 54%
“…Our findings support the utility of HDAC2 inhibitors in colorectal treatment. SCA, a powerful and specific HDAC2 inhibitor, has been demonstrated to effectively suppresses tumour progression both in vitro and in vivo 48,49 . In our study, aberrant HDAC2 overexpression led to the transcriptional silencing of NLRP3 and suppressed cancer cell pyroptosis.…”
Section: Discussionmentioning
confidence: 49%
“…CAY10683, an inhibitor of HDACs, in combination with imatinib. exerted synergistic effects on imatinib resistance by inhibiting HDAC2 and the PI3K/Akt signal transduction pathway in chronic myelogenous leukemia (CML) cells with imatinib resistance [107] .…”
Section: The Role Of Hdac2 In Anti-cancer Drug Resistancementioning
confidence: 99%
“…Interestingly, a combined therapy of santacruzamate A with tacedinaline showed growth inhibition, cell cycle progression changes, and apoptosis induction in the HepG2 and Huh7 cell lines. Additionally, Zhang, et al [ 145 ] showed that the combined treatment of santacruzamate A with imatinib exerted a synergistic effect on the inhibition of cell viability, induction of apoptosis, and cell cycle arrest in the G2/M phase in imatinib-resistant chronic myeloid leukemia (CML) cells. At the same time, it produced minimal effects on normal CD34 + cells.…”
Section: Marine Cyanobacterial Metabolites With Cytotoxic Antiprolife...mentioning
confidence: 99%